2014
DOI: 10.1016/j.lfs.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Dual endothelin receptor antagonism with bosentan reverses established vascular remodeling and dysfunctional angiogenesis in diabetic rats: Relevance to glycemic control

Abstract: Aims We have shown that diabetes causes cerebrovascular remodeling in part by the activation of the endothelin (ET-1) system in a glucose-dependent manner. We also reported increased yet dysfuctional cerebral angiogenesis in diabetes. Here, we tested the hypothesis that dual ET-1 receptor antagonism or glycemic control can reverse already established diabetes-induced vascular remodeling and neovascularization. Main Methods 18-week non-obese type-2 diabetic Goto-Kakizaki (GK) were treated with vehicle, metfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Given that DPP-4 inhibitors display pleiotropic effects independent of glycemic control (13, 14) and our previous study showed that inhibition of the ET system by bosentan also prevented and reversed dysfunctional cerebral angiogenesis in the GK model of diabetes (17), we next investigated the direct effects and interaction of linagliptin with ET-1 on proangiogenic properties of primary BMVECs isolated from control or diabetic animals. As we previously reported (16), BMVECs from diabetic GK rats have erratic migratory properties that resemble the chaotic vascularization seen in vivo and our current data show that linagliptin decreases tube formation and migration in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that DPP-4 inhibitors display pleiotropic effects independent of glycemic control (13, 14) and our previous study showed that inhibition of the ET system by bosentan also prevented and reversed dysfunctional cerebral angiogenesis in the GK model of diabetes (17), we next investigated the direct effects and interaction of linagliptin with ET-1 on proangiogenic properties of primary BMVECs isolated from control or diabetic animals. As we previously reported (16), BMVECs from diabetic GK rats have erratic migratory properties that resemble the chaotic vascularization seen in vivo and our current data show that linagliptin decreases tube formation and migration in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, bosentan alleviates increased neovascularization and leaky vessels in cerebrovascular system of a type 2-diabetic animal model and inhibits tumor vascularization and bone metastasis in an animal model of breast carcinoma cell metastasis [106,107]. This is also the case in SSc because the number of nailfold ramified capillaries, which reflect activated angiogenesis, is decreased after a one-year administration of bosentan [108].…”
Section: Bosentanmentioning
confidence: 95%
“…Elevation of ET-1 has been well documented in patients and experimental models in diabetes (Matsumoto et al, 2004; Takahashi et al, 1990). Dual endothelin receptor blockade prevents cerebrovascular dysfunction and improper neovascularization as well as improvement in hippocampal-based cognitive tasks in diabetes (Abdelsaid et al, 2014a, 2014b; Singh et al, 2014). Overexpression of endothelial ET-1 impairs BBB function and worsens cognitive dysfunction after ischemic injury (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%